Morphology and ion diffusion in PEDOT:Tos. A coarse grained molecular dynamics simulation. Issue 25 (14th June 2018) - Modarresi, Mohsen; Franco-Gonzalez, Juan Felipe; Zozoulenko, Igor
Abstract : A Martini coarse-grained Molecular Dynamics (MD) model for the doped conducting polymer poly(3, 4-ethylenedioxythiophene) (PEDOT) is developed. It is shown that the diffusion coefficients decrease exponentially as the hydration level is reduced. Abstract : A Martini coarse-grained Molecular Dynamics (MD) model for the doped conducting polymer poly(3, 4-ethylenedioxythiophene) (PEDOT) is developed. The morphology of PEDOT:Tos ( i.e. PEDOT doped with molecular tosylate) and its crystallization in aqueous solution for different oxidation levels were calculated using the developed method and compared with corresponding all atomistic MD simulations. The diffusion coefficients of Na + and Cl − ions in PEDOT:Tos are studied using the developed coarse-grained MD approach. It is shown that the diffusion coefficients decrease exponentially as the hydration level is reduced. It is also predicted that the diffusion coefficients decrease when the doping level of PEDOT is increased. The observed behavior is related to the evolution of water clusters and trapping of ions around the polymer matrix as the hydration level changes. The predicted behavior of the ionic diffusion coefficients can be tested experimentally, and we believe that molecular picture of ionic diffusion in PEDOT unraveled in the present study is instrumental for the design of polymeric materials and devices for better and enhanced performance.